CrIII, MnII and CoII Complexes with Schiff Base Ligand; Synthesis, Characterization, Physicochemical and Thermal Properties - Mezher, Mohammed Qays; Yousif, Enaam Ismail (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2026)
Synthesis and characterization of a Schiff base ligand (HL), derived from ((E)-3-((4-acetylphenyl)diazenyl)-2-hydroxy-1-naphthaldehyde) with 1-amino-4-nitrobenzene in a one-to-one molar ratio. This study aims to synthesize and characterize HL. Subsequently, the interaction of ligand with different metal ions involving chromium (III), manganese (II) and cobalt (II) in the ratio of one ligand to one metal, resulted in the isolation of tetra and hexa-coordinate monomeric compound have been fully characterized using analytical methods and spectroscopic methods involve elemental microanalysis, 1H and 13C (NMR), (FT-IR) spectroscopy, as well as electronic spectra and magnetic moment magnetic susceptibility along with mass spectroscopy, in addition, thermal analysis and conductivity measurements. The FTIR analysis showed the presence of functional groups, including carbonyl, imine, and azo, as well as vibrations (M-OH2), (M-O), (M-N), and (M-Cl). Mass spectrometry identified a deprotonated molecular ion ([M-H]+) for the ligand at m/z= 437.55 amu (1%). The electron spectra and magnetic moments: 3.80, 5.91, 4.66 BM for chromium, manganese, and cobalt complexes, respectively. It has been proposed that the chromium and manganese complexes adopt distorted octahedral geometries, whereas the cobalt complex adopts a tetrahedral geometry.